Behavior Prevention of STIs (Sexually Transmitted Infections) and HIV / AIDS on Gay Non-Injection drug users in Kediri District - Siti Asiyah Siti Asiyah Siti Asiyah (STIKES Karya Husada Kediri, 2014)
The majority of gay anal sex, anal anatomy is not so easy to produce lubricants that trauma is a risk of transmission of STIs and HIV, especially when not using a condom, condom use is inconsistent factor is including the non- injection drug users.This studies Qualitative research with in-depth interviews on the main informed 5 gay non Injection drug users, supporting informant chairman of the gay community, VCT clinic staff, secretaries KPAD and Kasi P2ML Kediri district health office, and FGD on 6 gay community members with an analysis of the data analysis browse by theme ( thematic content analysis).Results of studies addressing the sexual behavior of all respondents have multiple sexual partners, condom appliances inconsistency occurs on all respondents and visits to the VCT clinic had largely been but has not been able to routinely every 3 months using a main.For it needs to be taken preventive measures before the issue of drug use in gay in Kediri be great.